Protective effects of the aqueous extract of Crocus sativus against ethylene glycol induced nephrolithiasis in rats - Amin, Bahareh (EXCLI J, 2015)
This study evaluated the possible protective effect of Crocus sativus L. (saffron) in the treatment of renal calculi. Aqueous extract of saffron (25, 50 and 100 mg/kg, daily) was administered intraperitoneally in two regimens of protective or curative, using male Wistar rats. Urolithiasis was induced by ethylene glycol (% 0.75) in drinking water. Urine was collected for biochemical analysis and the kidneys were prepared for total lipid peroxide and histological evaluation. Ethylene glycol feeding resulted in an increased urine output, renal excretion of oxalate and decreased excretion of citrate and magnesium. Saffron did not show diuretic effect; however, it significantly reduced the elevated urinary oxalate in prophylactic (50 and 100 mg/kg) and curative (100 mg/kg) studies. Only the high dose of prophylactic regimen restored citrate concentration of urine. Increased number of calcium oxalate crystals deposits in the kidney tissue of calculogenic rats was significantly reverted by the prophylactic and high dose of curative saffron treatment. Malondialdehyde (MDA, a lipid peroxidation product) in the kidneys was increased following the lithogenic treatment; however, prophylactic (50, 100 mg/kg) and curative (100 mg/kg) regimens with saffron reduced the elevated levels of MDA. Results in the current study indicate that saffron can protect against ethylene glycol induced calcium oxalate (CaOx) nephrolithiasis. The mechanisms underlying this effect are mediated possibly through effect on the urinary concentration of stone-forming constituents and an antioxidant effect.